1994
DOI: 10.1159/000106735
|View full text |Cite
|
Sign up to set email alerts
|

Cambridge Neuropsychological Test Automated Battery (CANTAB): A Factor Analytic Study of a Large Sample of Normal Elderly Volunteers

Abstract: The CANTAB battery was administered to a large group (n = 787) of elderly volunteers in the age range from 55 to 80 years. This battery, which is based on tests used to identify the neural substrates of learning and memory in non-human primates, has now been extensively used in the assessment of various forms of dementia and also validated on patients with neurosurgical lesions of the frontal and temporal lobes. The tests employed were pattern and spatial recognition, simultaneous and delayed matching to sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
686
2
12

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 723 publications
(736 citation statements)
references
References 25 publications
17
686
2
12
Order By: Relevance
“…Also, a large meta-analysis of age and sex differences by Meinz and Salthouse (1998) noted superior performance by men for spatial tests, primary and working memory tests, and tests of reasoning. However, our findings are not consistent with those of Robbins et al (1994), who examined 787 adults aged 55-80 y and found no sex differences on our measures of either PRM or MTS. The present 5-CRT results also contrast with Meinz and Salthouse's finding of greater perceptual speed in women than in men.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Also, a large meta-analysis of age and sex differences by Meinz and Salthouse (1998) noted superior performance by men for spatial tests, primary and working memory tests, and tests of reasoning. However, our findings are not consistent with those of Robbins et al (1994), who examined 787 adults aged 55-80 y and found no sex differences on our measures of either PRM or MTS. The present 5-CRT results also contrast with Meinz and Salthouse's finding of greater perceptual speed in women than in men.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, there was clear evidence of age-related decline in visual memory (as assessed by PRM), working memory (as assessed by SSP) and attention (as assessed by 5-CRT and MTS) in the ZENITH sample at baseline. These findings are consistent with previous results from studies that have administered tests from the CANTAB battery to healthy older adults and found age deficits (eg, Nettelbeck & Rabbitt, 1992;Robbins et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On Day 2, patients were administered a cognitive battery to measure processing speed, working memory, inductive reasoning, long-term memory, prospective memory, and verbal ability (see Table 1). [33][34][35][36][37][38][39][40][41][42] Multiple tests were used for each cognitive domain, allowing a latent trait to be extracted. Northwestern University's Institutional Review Board approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…Tests shown to be sensitive to fronto-striatal or temporal lobe damage were employed from a standardized and computerised neuropsychological test battery (CANTAB) (Robbins et al 1994 together with other related variants (Iddon et al 1998;Owen et al 1995a). The CANTAB battery has been used in a wide variety of relevant patient groups, including patients with neurosurgical excisions of the prefrontal cortex or temporal lobe (Owen et al 1995b), basal ganglia disorders such as Parkinson's (e.g., Downes et al 1989;Owen et al 1992), and Huntington's disease (e.g., Lawrence et al 1996), as well as depression, schizophrenia (Elliott et al 1998), and dementia (Sahakian et al 1988).…”
mentioning
confidence: 99%